Modelling of the acoustic properties of the larger human blood vessel - Borisyuk, A.O. (Інститут гідромеханіки НАН України, 1998)
An acoustic model of a larger human blood vessel is developed in order to study the properties of an acoustic field produced by a stenotic narrowing in the vessel. This model takes into account the basic features of noise generation and propagation in human thorax from the source (turbulent pressure fluctuations in blood flow) to the receiver resting on the skin. The low Mach number turbulent wall pressure models by Corcos, Chase, Ffowcs Williams and Smol'yakov-Tkachenko are used for describing the random noise sources in the vessel. The obtained relationships permit analyzing of dependence of the acoustic field in the thorax on the blood flow and vessel parameters, and give the possibility of finding the characteristic signs of presence of a stenotic narrowing in the vessel.